Memory and reparation in Higher Education: an analysis of Universities’ Truth Commissions in São Paulo (Tempo e Argumento, 2021)
The article initially analyzes the installation and performance dynamics of University Truth Commissions created in different Brazilian universities since 2012. However, public and private institutions in the state of São Paulo were chosen as the main object of analysis. For this purpose, it takes as an empirical basis the published reports from which it seeks to identify characteristics and conditions of implementation, adherence of the university community and the correlation of favorable and opposite forces to its installation. Special attention was given to the recommendations made by the Commissions. The documentary analysis is situated in a context in which the juncture of the National and State Commissions, inserted in the time frame from 2012 to 2018, is taken into account. Such demarcation considered 2012 as the starting year, when the first University Commissions were finally established. And 2018 for being the closing year for the work of the University Commission of the University of São Paulo (USP), the last in the state.